2020
DOI: 10.1158/0008-5472.can-19-2115
|View full text |Cite
|
Sign up to set email alerts
|

An LTR Retrotransposon-Derived Long Noncoding RNA lncMER52A Promotes Hepatocellular Carcinoma Progression by Binding p120-Catenin

Abstract: Long terminal repeat (LTR) retrotransposons are a major class of transposable elements, accounting for 8.67% of the human genome. LTRs can serve as regulatory sequences and drive transcription of tissue or cancer-specific transcripts. However, the role of these LTR-activated transcripts, especially long noncoding RNAs (lncRNA), in cancer development remains largely unexplored. Here, we identified a novel lncRNA derived from MER52A retrotransposons (lncMER52A) that was exclusively expressed in hepatocellular ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 45 publications
0
41
0
3
Order By: Relevance
“…The malignant transformation of tumor is mainly related to over-activation or over-expression of Rac1. Up to now, the increase of Rac1 expression has been detected in different types of cancers, such as BC, lung cancer, colorectal cancer, gastric cancer, prostate cancer, hepatocellular carcinoma and ovarian cancer (40)(41)(42)(43)(44)(45)(46). The activity of Rac1 is also related to many posttranslational modifications, such as phosphorylation (Tyr64, Ser71), ubiquitination (Lys147, K166R), lipidation, and adenylation (Y32) (47)(48)(49)(50)(51)(52)(53).…”
Section: The Expression and Clinical Significance Of Rac1 In Tumorsmentioning
confidence: 99%
“…The malignant transformation of tumor is mainly related to over-activation or over-expression of Rac1. Up to now, the increase of Rac1 expression has been detected in different types of cancers, such as BC, lung cancer, colorectal cancer, gastric cancer, prostate cancer, hepatocellular carcinoma and ovarian cancer (40)(41)(42)(43)(44)(45)(46). The activity of Rac1 is also related to many posttranslational modifications, such as phosphorylation (Tyr64, Ser71), ubiquitination (Lys147, K166R), lipidation, and adenylation (Y32) (47)(48)(49)(50)(51)(52)(53).…”
Section: The Expression and Clinical Significance Of Rac1 In Tumorsmentioning
confidence: 99%
“…The results reported here that YY1 has importance in promoting hepatocarcinogenesis is consistent with the previous reports. Wu et al showed YY1 transcription factor promoted HCC progression by activating lncMER52A and then stabilized p120-catenin the downstream effector of lncMER52A [25] . YY1 promoted HCC cells proliferation and migration via facilitating linc01134/miR-324-5p/IGF2BP1, and IGF2BP1 stabilizing YY1 mRNA expression, forming a positive feedback loop [26] .…”
Section: Discussionmentioning
confidence: 99%
“…After treated with or without VE821 for 48 h, MHCC-97H cells in different dish were added with cycloheximide (CHX, 50 g/ml) at the same time. At indicted time points (0, 5,10,15,20,25,30,35,40 and 45 h), protein samples were collected and then analyzed by western blotting assay.…”
Section: Protein Degradation Analysismentioning
confidence: 99%
“…A third significant aspect of HERV reactivation is associated with the expression of long noncoding RNAs (lncRNAs), as recently observed in hepatocellular carcinoma ( Table 2 ) [ 27 , 34 ].…”
Section: Human Endogenous Retrovirusesmentioning
confidence: 99%
“…Indeed, HCC development is a multistep process associated with genetic alterations, as well as dysregulated gene expression. However, recent findings indicate a dysregulated expression of LTR-derived noncoding RNAs (ncRNAs) in HCC [ 27 , 34 ].…”
Section: Hervs and Liver Cancermentioning
confidence: 99%